Pengembangan Bahan Ajar Berbasis CD Interaktif Power Point Untuk Meningkatkan Hasil Belajar Siswa - Warkintin Warkintin; Yohanes Berkhamas Mulyadi (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
This study aims to describe the development of interactive CD learning materials based on power point to improve students’ learning outcomes within the topic of production technology, communication and transportation in grade IV. The research methods used are research and development, consisting of the preliminary study, model development, and model testing. The results show that the interactive CD learning materials developed are eligible according to the development steps. The results of media validation and the results of material validation were shown with average score of 79,8% and 87,2% respectively. The students' responses to interactive learning materials scored 81.75% on small-scale trials while large-scale trials obtained a score of 85%. Then the teacher's response scored 71.7% and 80.48% respectively. Based on the value obtained, then the interactive CD teaching materials are feasible to be applied to grade 4 elementary school students. Based on the test results of the student learning on small-scale, it showed that 63% of students passed with the score ≥75. While on a large-scale, 100% of the students passed and scored ≥75. Thus, it can be concluded that the development of interactive teaching materials is appropriate for students in grade IV of elementary school.